Superficial Bladder Cancer Recurrence on First Check Cystoscopy after Transurethral Resection (TURBT). - Insar Hussain Malik, Wajeed Gul Bangash, Sajid Mumtaz Qazi. (Journal of Rawalpindi Medical College, 2016)
Background:To determine the frequency of recurrence of superficial tumours on first check cystoscopy i.e. 3 months after complete resection of tumour. Methods: In this descriptive study adult male and female patients (n=41) presenting with a superficial transitional cell carcinoma of urinary bladder were included and complete resection of the tumour was done and tissue sent for histopathology. Patients with Superficial T.C.C (confirmed by histopathology) were followed up, after three months by cystoscopy and findings noted. Any tumour growth on the same or new location was resected again and sent to the same histopathologist for examination and confirmation of TCC. All the above information was recorded and entered into a structured proforma. Results: Majority (80.5%) were male . The age of patients ranged from 28 to 85 years with a mean of 59± 11.5 yrars.. The T-stage at presentation was pTa in 11 (27%) patients and pT1 in 30 (73%) patients. The histological grade of tumour at presentation was G-I in 16 (39%), G-II in 10 (24%) and G-III in 15 (37%) patients. First check cystoscopy was done 3 months after TURBT. In which 28 (68%) patients showed recurrence of tumour while the rest, i.e. 13 (32%) showed disease free status. Out of 28 cases with recurrence of tumour, 2 (5%) cases showed pTa and 26 (63%) showed pT1. The recurrent histological G-I, G-II and G-II were 5, 8 and 15 respectively. Conclusion: Recurrence of superficial transitional cell carcinoma at first check cystoscopy is high and has a predictive value for future recurrence of the disease.